Role of oxidative stress and insulin resistance in disease severity of non-alcoholic fatty liver disease - Köroğlu, Emine; Canbakan, Billur; Atay, Kadri; Hatemi, İbrahim and Tuncer, Murat and Dobrucalı, Ahmet and Sonsuz, Abdullah and Gültepe, İlhami and Şentürk, Hakan (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: Oxidative stress and insulin resistance (IR) are major contributors in the pathogenesis of non-alcoholic fatty liver disease (NAFLD). The purpose of this study was to find the relation between oxidative stress parameters and histopathological findings in NAFLD patients with and without insulin resistance (IR). Materials and Methods: Thirty-two patients with no alcohol intake and biopsy-proven diagnosis of NAFLD were studied (M/F: 17/15; mean age 46.5±11.4 years). Twenty-one NAFLD patients with IR were compared with 11 patients without IR. The fasting insulin level was measured, and the insulin resistance index was calculated using the homeostasis model assessment (HOMA) method. Malondialdehyde (MDA) and superoxide dismutase (SOD) activities were measured in tissue and serum specimens. Glutathione (GH) was measured in tissue homogenates. Nitric oxide (NO), vitamin E and C levels were measured in serum. Results: Patients with IR had significantly higher tissue MDA levels (p=0.001) and significantly decreased tissue SOD and GH levels (p=0.001 and 0.002, respectively) than those without IR. The steatosis grade, necroinflammatory grade and stage were significantly higher in patients with IR (p=0.035, 0.003 and 0.001, respectively). HOMA IR significantly correlated with the necroinflammatory grade, stage, tissue MDA, SOD and GH (p=0.013, 0.001, 0.008, 0.001 and 0.001, respectively). Serum MDA (β=1.88, p=0.002), serum SOD (β=0.57, p=0.006), tissue MDA (β=0.22, p=0.006), tissue SOD (β=1.48, p=0.071) and stage (β=2.81, p=0.003) were independently associated with increased HOMA IR. Increased MDA [OR: 1.51; 95% CI: (1.03–2.22); p=0.034] was a risk factor for non-alcoholic steatohepatitis (NASH), and increased SOD activity had a preventive effect against NASH [OR: 0.008; 95% CI: (0.001–0.98); p=0.04]. Conclusion: This study shows that insulin resistance in NAFLD correlates with enhanced oxidative stress. Histopathological disease severity significantly correlated with oxidative stress parameters. These data show that NAFLD patients with IR may have increased risk for disease progression.